2015
DOI: 10.2217/nnm.15.77
|View full text |Cite
|
Sign up to set email alerts
|

Tetronic ® 904-Containing Polymeric Micelles Overcome the Overexpression of ABCG2 in the Blood–Brain Barrier of Rats and Boost the Penetration of the Antiretroviral Efavirenz into the CNS

Abstract: Tetronic 904-containing polymeric micelles overcame the overexpression of ABCG2 in the BBB caused by chronic administration of EFV then boosting its penetration into the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In this sense, no histologic alterations, at least at striatal level, were found in fetal brains exposed in utero to AZT in our model (Fig 1 C and F). An induction of ABCG2 could be attained by sustained substrate exposure, as we previously observed for the overexpression of ABCG2 in small intestine and blood-brain barrier caused by efavirenz (Peroni et al, 2011;Roma et al, 2015) as well as in the placenta and in the fetal brain (present work, Fig 1A and 1B). Moreover, immunofluorescence showed that an specific mark for ABCG2 localized in blood vessels structures in the cortex fetal brain ( Fig 1C-F; (Ek et al, 2010) confirms the presence of this transporter in the developing brainbarrier exerting efflux mechanisms.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 2 more Smart Citations
“…In this sense, no histologic alterations, at least at striatal level, were found in fetal brains exposed in utero to AZT in our model (Fig 1 C and F). An induction of ABCG2 could be attained by sustained substrate exposure, as we previously observed for the overexpression of ABCG2 in small intestine and blood-brain barrier caused by efavirenz (Peroni et al, 2011;Roma et al, 2015) as well as in the placenta and in the fetal brain (present work, Fig 1A and 1B). Moreover, immunofluorescence showed that an specific mark for ABCG2 localized in blood vessels structures in the cortex fetal brain ( Fig 1C-F; (Ek et al, 2010) confirms the presence of this transporter in the developing brainbarrier exerting efflux mechanisms.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Moreover, it was shown that the efflux of antiretroviral drugs by ABCG2 seems to become of relevance whether a high density of molecules are present in the cell membrane, as occurred either in transfected or transformed cell lines (Pan et al, 2007;Wang et al, 2004Wang et al, , 2003Weiss et al, 2007) or under in vivo repeated exposure to a substrate as efavirenz (Peroni et al, 2011;Roma et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation